A 10-hour within-participant magnetoencephalography narrative dataset to test models of language comprehension - Kristijan Armeni; Umut Güçlü; Marcel van Gerven; Jan-Mathijs Schoffelen (Scientific Data, 2022)
Measurement(s) brain activity measurement Technology Type(s) Magnetoencephalography Factor Type(s) auditory story Sample Characteristic - Organism Homo sapien